Can Concept Maps Support Medical Students Learning From Simulation? - Parker-Jones, Christine; Pilkingto, Rachel (Theoria et Historia Scientiarum, 2007)
Medical students need to acquire critical thinking skills to support diagnostic reasoning. Simulations can be particularly useful in providing a meaningful context in which students can both acquire conceptual models of complex systems and practise diagnostic reasoning. However, engagement with simulations can be shallow and their foil potential for learning may not be realised unless students are supported with appropriate active tasks and scenarios. This paper examines the use of Concept Maps as an aid to learning whilst interacting with a simulation of calcium metabolism. The paper reviews the ways in which Concept Maps might plausibly assist students engaged in the problem-solving and planning activities associated with diagnosis and treatment of calcium imbalance. A study is reported which indicates that Concept Maps can be an aid to learning both alongside the use of simulation and in their own right. Concept Maps also provide useful insights into the completeness and consistency of students’ mental models following interaction with a simulation model.